Rheumatology Training in Latin America: A Collaborative Study by the Pan American League of Associations for Rheumatology. Issue 2 (March 2022) - Fernández-Ávila, Daniel G.; Patino-Hernandez, Daniela; Kowalskii, Sergio; Vargas-Caselles, Alfredo; Sapag, Ana Maria; Cachafeiro-Vilar, Antonio; Meléndez, Belia; Santiago-Pastelín, Carlos; Graf, Cesar; Rossetto, Chayanne; Palleiro, Daniel; Trincado, Daniela; et al.
Abstract : Background/Objective: Demand for rheumatology care has steadily increased in recent years. The number of specialists in this field, however, seems insufficient. No recent studies have diagnosed the attributes of rheumatology training in Latin America. Methods: This is a descriptive cross-sectional study. We obtained data on each country through local rheumatologists of the Pan-American League Against Rheumatism, who acted as principal investigators for participating countries. Our sample was analyzed and described through means and standard deviations or through frequencies and percentages, depending on the variable. Results: Countries with the most rheumatology-training programs were Brazil (n = 50), Argentina (n = 18), and Mexico (n = 15). Ecuador, Honduras, and Nicaragua do not have rheumatology-training programs. The countries with the most available slots for rheumatology residents were Brazil (n = 126) and Argentina (n = 36). To be admitted into rheumatology training, candidates were required to have completed graduate studies in internal medicine in 42.1% of the programs. In 8 countries (42.1%), residents are not required to pay tuition; the median cost of tuition in the remaining countries is US $528 (interquartile range, US $2153). Conclusions: Conditions associated with rheumatology training in Latin America vary. Significant differences exist in income and tuition fees for residents, for example, and 4 countries in Latin America do not currently offer programs. Information collected in this study will be useful when comparing the status of rheumatology services offered in Latin America with those in other countries. Most countries require a wider offering of rheumatology-training programs, as well as more available slots.